Augmentation of Vascular Endothelial Barrier Function by Heparin and Low Molecular Weight Heparin - Bannon, P G; Kim, Mi-Jurng; Dean, R T; Dawes, J (Thrombosis and Haemostasis, 1995)
Glycosaminoglycans (GAGs) are an important component of endothelial barrier function. Early passage human umbilical vein endothelial cells were grown to confluence on transparent micropore filters and barrier function assessed as transendothelial electrical resistance (TEER) and permeability to albumin and sucrose. Unfractionated heparin and the LMW heparin Clexane decreased endothelial permeability to both sucrose and albumin and increased TEER. Chondroitin 6-sulphate also augmented barrier function, but other GAGs had no effect. Interleukin-1 increased permeability to albumin and sucrose and decreased TEER. Although heparin attenuated the effect of IL-1 on TEER and sucrose permeability, it could not restore the barrier to albumin transfer. Denuded endothelial matrix presented a negligible barrier, which was not enhanced by heparin. When sulphation of endogenous GAGs was inhibited by chlorate, barrier function was compromised and was not restored by exogenous heparin. Thus heparin enhances the barrier function of resting endothelium, but cannot completely overcome the increased permeability resulting from exposure to IL-1 or substitute for endogenous GAGs.